Application of Finite Difference Method in Simulating 2D Partial Dam-break Flow with an Obstacle - Hafiyyan, Qalbi; Nirmala, Azwa; MS, Murad; Sumiyattinah, Sumiyattinah; Bachtiar, Vivi; Yusuf, Muhammad Yusuf (Indonesian Journal of Multidisciplinary Science, 2023)
A numerical model capable of simulating the dam-break flow is required to reduce the detrimental impact on the downstream area of the dam. This study aims to see how the characteristics and patterns of flow due to partial dam failure and the presence of an obstacle in the floodplain. In real life, the obstacle can be considered as a building. In this research, a model based on the FTCS method was developed with the addition of a Hansen numerical filter. This model is known as the FTCS-Hansen model. The Hansen filter in this study is used to enhance the numerical of the model and reduce oscillations due to shock waves. The FTCS-Hansen model simulates a 2D partial dam break with an obstacle. The simulation results are compared with other simulation results from previous studies. This comparison intends to see the performance of the FTCS-Hansen model. The results show good agreement between the FTCS-Hansen model and other numerical models. In addition, the complicated dam-break flow characteristics due to the presence of an obstacle (reflection and diffraction) can also be well captured by the FTCS-Hansen model.